Edukasi tentang Covid-19 dengan Membaca Nyaring Komik Seri Korona kepada Siswa Sekolah Dasar Muhammadiyah Banda Aceh - Yusuf, Wardiati (Empowerment : Jurnal Pengabdian Masyarakat, 2022)
Covid-19 has infected all age groups. Children and teenagers, however, are the most vulnerable group because they have lack knowledge about Covid-19 dan how to prevent the infection. Many research findings have shown that children and teenagers in Indonesia have the highest Covid-19 fatality rate in the world. It indicates that health promotion regarding Covid-19 to these groups is ineffective and insufficient. This activity aims to educate children (1st and 2nd-grade students) in Muhammadiyah Elementary School in Banda Aceh regarding Covid-19 through reading aloud comic Korona series. The health promotion method implemented in this activity was health promotion in a small group. The participants were 1st and 2nd-grade students in Muhammadiyah Elementary School in Banda Aceh. The total number of participants was 28 students. The result showed that the students have high enthusiasm to participate in reading aloud Korona series comics and also actively asked many questions related to Covid-19. The parties responsible for health promotion are suggested to carry out similar activities on an ongoing basis. Therefore, students have adequate knowledge and are well-informed about Covid-19 transmission prevention.